The Role of Entrepreneurship Education and Self-efficacy on Students’ Entrepreneurial Intention - Baba, Mukhtar; Audu, Ibrahim (Kashere Journal of Management Sciences, 2024)
This study examines the determinants of entrepreneurial intention among undergraduate students at Nigerian Universities. Primarily, this study explored the role entrepreneurial education, and self-efficacy on students’ intention to become entrepreneurs. Accordingly, 242 business related students from Federal University of Kashere were participated in this study. Using Statistical Package for the Social Sciences (SPSS), multiple regressions linear analysis was conducted to test the study hypotheses. The findings show that all the independent variables; entrepreneurial education and self-efficacy are significantly and positively related to entrepreneurial intention (β=, .270 and .191 t= 4.05 and 2.86 p= >>0.00and >0.04 respectively). Besides, the reliability test for all the variables was also conducted which shows the Cronbach Alpha for EI 0.83,, EEDU 0.70 and SE 0.70.